A new approach to teaching architectural and urban design: Reformulation of city spaces with virtual tools and long-distance influences (EAAE Annual Conference Proceedings, 2023)
The spatial interventions in city heritage areas today require careful consideration of many issues. Solutions require a deep understanding of social, cultural, economic, architectural, historical, and more that make up the fabric of cities. Sometimes, more than just knowledge and design skills, what is required is to anticipate, to compromise a vision of possible memories and future recollections. The paper presents a teaching method elaborated and tested during an international student design workshop in Tel Aviv (Israel) and Cracow (Poland).